Constitutional Intolerance in Europe: A Review Essay of "Constitutional Intolerance: The Fashioning of the Other in Europe’s Constitutional Repertoires" by Mariëtta van der Tol - Potappel, Maurits ca. 20./21. Jh. (Philosophia reformata, 2025)
In this review essay, I discuss the book Constitutional Intolerance, written by Mariëtta van der Tol. Its central thesis is that intolerance is embedded in European constitutions, both in liberal and in illiberal regimes. Building upon historical analysis of European constitutions and taking into account such concepts as time, space, and othering, the book presents four case studies of liberal- and illiberal-leaning states. Although the book is richly documented and reflects a long study of constitutionalism, I criticize its central thesis and argue that various important forms of intolerance in liberal-leaning states have been left out of the analysis.